Transactional environmental support system design global solutions - Papathanasiou, Jason. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book emphasizes the increasing potential for environmental decision support while directly addressing some of the challenges that must be overcome"--Provided by publisher.